Peningkatan Pemahaman Siswa tentang Makanan Sehat dan Bergizi melalui Pembelajaran Berbasis Media Gambar di Kelas IV MI Al-Barokah - Siti Amanda; Muhammad Suwignyo Prayogo; Aprilia Yuliantika; Maimunah Maimunah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study originated from the issue of students’ limited comprehension of healthy and nutritious food concepts, which influences their lack of awareness in practicing a balanced diet in daily life. The conventional learning approach with minimal integration of visual aids has made students less engaged and hindered their overall understanding of the material. The primary objective of this research is to enhance fourth-grade students’ understanding of healthy and nutritious food at MI Al-Barokah through the application of picture-based learning media. Planing, implementation, observation, and reflection were the two stages of Classroom Action Research (CAR) that was used in the research. The participants were 25 fourth-grade students of MI Al-Barokah. Data were gathered through observations, interviews, and achievement tests, and analyzed using both qualitative and quantitative descriptive methods. The findings revealed a marked improvement in students’ understanding after the introduction of picture media, as reflected in the increasing average learning scores across cycles, along with greater motivation, participation, and engagement in classroom activities. The integration of picture media proved effective in facilitating a clearer, more engaging, and meaningful grasp of healthy and nutritious food concepts. These results suggest that picture-based instructional media can serve as a valuable strategy to improve the quality of thematic learning in elementary education, especially in lessons concerning healthy living and balanced nutrition.